Multi-enzyme production by pure and mixed cultures of Saccharomyces and non-Saccharomyces yeasts during wine fermentation - Maturano, Yolanda Paola; Rodriguez Assaf, Leticia Anahi; Toro, María Eugenia; Nally, María Cristina; Vallejo, Martha Dina; Castellanos de Figueroa, Lucía Inés; Combina, Mariana; Vazquez, Fabio (Elsevier, 2019)
Saccharomyces and non-Saccharomyces yeasts release enzymes that are able to transform neutral compounds of grape berries into active aromatic compounds, a process that enhances the sensory attributes of wines. So far, there exists only little information about enzymatic activity in mixed cultures of Saccharomyces and non-Saccharomyces during grape must fermentations. The aim of the present work was to determine the ability of yeasts to produce extracellular enzymes of enological relevance (β-glucosidases, pectinases, proteases, amylases or xylanases) in pure and mixed Saccharomyces/non-Saccharomyces cultures during fermentation. Pure and mixed cultures of Saccharomyces cerevisiae BSc562, Hanseniaspora vinae BHv438 and Torulaspora delbrueckii BTd259 were assayed: 1% S. cerevisiae/99% H. vinae, 10% S. cerevisiae/90% H. vinae, 1% S. cerevisiae/99% T. delbrueckii and 10% S. cerevisiae/90% T. delbrueckii. Microvinifications were carried out with fresh must without pressing from Vitis vinifera L. c.v. Pedro Jiménez, an autochthonous variety from Argentina. Non-Saccharomyces species survived during 15–18 days (BTd259) or until the end of the fermentation (BHv438) and influenced enzymatic profiles of mixed cultures. The results suggest that high concentrations of sugars did not affect enzymatic activity. β-Glucosidase and pectinase activities seemed to be adversely affected by an increase in ethanol: activity diminished with increasing fermentation time. Throughout the fermentation, Saccharomyces and non-Saccharomyces isolates assayed produced a broad range of enzymes of enological interest that catalyze hydrolysis of polymers present in grape juice. Vinifications carried out by a pure or mixed culture of BTd259 (99% of T. delbrueckii) showed the highest production of all enzymes assayed except for β-glucosidase. In mixed cultures, S. cerevisiae outgrew H. vinae, and T. delbrueckii was only detected until halfway the fermentation process. Nevertheless, their secreted enzymes could be detected throughout the fermentation process. Our results may contribute to a better understanding of the microbial interactions and the influence of some enzymes on vinification environments.